roluci
18

# Resolva as equações: a) 2 x + 5 = 27 b) 4 x - 8 = 2 x + 6 c) 7 x + 1 = 6 x + 6 d) 5 x - 3 = 2 x - 9 e) 4 x - 7 + x = 1 f) 3 - 2 x = 4 x g) 9 - x = x + 10 h) - 2 x + 7 = 4 x + 5 i) 3 x - 20 = x + 80 j) 5 x + 50 = 3 x + 290

(2) Respostas
Kayosantos

a) 2x + 5 = 27 2x = 27 - 5 2x = 22 x = 22/2 x = 11 b) 4x - 8 = 2x + 6 4x - 2x = 6 + 8 2x = 14 x = 14/2 x = 7 c) 7x + 1 = 6x + 6 7x - 6x = 6 - 1 x = 5 d) 5x - 3 = 2x - 9 5x - 2x = - 9 + 3 3x = - 6 x = - 6/3 x = - 2 e) 4x - 7 + x = 1 4x + x = 1 + 7 5x = 8 x = 8/5 f) 3 - 2x = 4x - 2x - 4x = - 3 - 6x = - 3 (-1) 6x = 3 x = 3/6 x = 1/2 ou x = 0,5 g) 9 - x = x + 10 - x - x = 10 - 9 - 2x = 1 (-1) 2x = - 1 x = - 1/2 ou x = - 0,5 h) - 2x + 7 = 4x + 5 - 2x - 4x = 5 - 7 - 6x = - 2 (-1) 6x = 2 x = 2/6 x = 1/3 i) 3x - 20 = x + 80 3x - x = 80 + 20 2x = 100 x = 100/2 x = 50 j) 5x + 50 = 3x + 290 5x - 3x = 290 - 50 2x = 240 x = 240/2 x = 120

nrs2011Nilson

a) 2 x + 5 = 27     2x = 27 - 5    2x = 22    x = 11 b) 4 x - 8 = 2 x + 6      4x - 2x = 6 + 8      2x = 14     x = 7 c) 7 x + 1 = 6 x + 6     7x - 6x = 6 - 1       x = 5 d) 5 x - 3 = 2 x - 9     5x - 2x = -9 +3      3x = -6      x = -2 e) 4 x - 7 + x = 1     5x = 1 + 7      5x = 8      x = 8/5 f) 3 - 2 x = 4 x      3 = 6x      x = 3/6      x = 1/2 g) 9 - x = x + 10     -x - x = 10 - 9     -2x = 1       x = -1/2 h) - 2 x + 7 = 4 x + 5         -2x - 4x = 5 - 7          -6x = -2            x = 2/6            x = 1/3 i) 3 x - 20 = x + 80      3x - x = 80 + 20      4x = 100        x = 25 j) 5 x + 50 = 3 x + 290    5x - 3x = 290 - 50      2x = 240      x = 120